2015
DOI: 10.1039/c5ra19326e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing temperature on the structure of carbon encapsulated Fe3O4 nanospheres

Abstract: Yolk–shell structured Fe3O4@C was obtained at 600 °C. A possible evolution mechanism of core–shell to yolk–shell Fe3O4@C is elaborated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The effect of purification also decreased the intensity of Fe3O4 and Fe2O3, suggesting that it influences the magnetization of the purified products. Moreover, the purification effect of CMNs-ED impacts the reduced intensity of the amorphous carbon diffraction peak at 2θ 21.36° (Shi et al, 2015). The magnetic property of CMNs-ED before purification, CMNs-ED purified by water, and CMNs-ED purified by immersion in toluene followed by annealing treatment was investigated with a vibrating sample magnetometer (VSM).…”
Section: Resultsmentioning
confidence: 99%
“…The effect of purification also decreased the intensity of Fe3O4 and Fe2O3, suggesting that it influences the magnetization of the purified products. Moreover, the purification effect of CMNs-ED impacts the reduced intensity of the amorphous carbon diffraction peak at 2θ 21.36° (Shi et al, 2015). The magnetic property of CMNs-ED before purification, CMNs-ED purified by water, and CMNs-ED purified by immersion in toluene followed by annealing treatment was investigated with a vibrating sample magnetometer (VSM).…”
Section: Resultsmentioning
confidence: 99%
“…The annealing temperature usually improves the surface pore structure of CNSs effectively, while easily causing the thermal cracking of surface oxygen-containing functional groups. For the purpose of constructing abundant pore structure on the surface and making no effect on the subsequent grafting reaction, four different annealing temperatures were investigated combining Fourier transform infrared (FT-IR) analysis with BET result. Figure S1 displays the FT-IR spectra of CNS and PCNS at different annealing temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier, we have shown that upon annealing in vacuum, oleic acid coated Fe 3 O 4 nanoparticles get reduced into metallic a-Fe at 500°C and into anti-ferromagnetic FeO phases at 700°C. 32 Recently, Shi et al 45 showed that the structure of carbon encapsulated individual Fe 3 O 4 nanoparticles under inert annealing conditions is stable up to 600°C. Indeed, carbon encapsulated Fe 3 O 4 reduced into Fe and Fe 3 C at 700°C due to carbothermic reduction process.…”
Section: Resultsmentioning
confidence: 99%